Frequency and Manifestations of Autoimmunity Among Children Registered in the Kuwait National Primary Immunodeficiency Registry - Massaad, Michel J.; Zainal, Mohammad; Al-Herz, Waleed (Frontiers in Immunology, 2020)
Objectives: To present a prospective report on the characteristics of autoimmune manifestations in patients with primary immunodeficient children registered in the Kuwait National PIDs Registry (KNPIDR). Methods: The data were obtained from the Kuwait National Primary Immunodeficiency Disorders Registry during the period of January 2004 to December 2019. Results: A total of 286 PID children were registered in KNPIDR during the study period with a predominance of immunodeficiencies affecting cellular and humoral immunity followed by combined immunodeficiencies with associated syndromic features and diseases of immune dysregulation. Fifty-seven (19.9%) patients presented with a total of 107 autoimmune manifestations. There was no significant statistical association between autoimmune manifestations and gender. Patients with autoimmune manifestations were older at onset of PID symptoms compared to those with no such manifestations, but this did not reach level of significance. The diagnosis delay was longer in patients with autoimmune manifestations compared to those with no such manifestations (p-value = 0.038). 47% of these manifestations were among the presenting symptoms while 53% were documented later during the course of the disease. 57% of the patients developed 1 autoimmune manifestation, 30% developed 2 such manifestations, and 16% had ≥ 3 autoimmune manifestations. The most common autoimmune manifestation was cytopenia, followed by gastrointestinal manifestations and manifestations of the skin, hair, and nails. Autoimmune cytopenia were more common in patients with immune dysregulation syndromes, while gastrointestinal and skin manifestations predominate in patients with immunodeficiencies affecting cellular and humoral immunity and endocrine manifestations were more common in immune dysregulation syndromes. There were significant statistical associations between developing autoimmune manifestations and death as well as PID categories, being more common in patients with immune dysregulation. The frequency of autoimmunity was high among patients with RAG, WAS, STAT5b, NF-B2, Fas, FasL, LRBA, APECED, IL-10, and C4 deficiencies. Conclusions: Autoimmunity is frequent in patients with PIDs in Kuwait. This should prompt the suspicion of a PID in patients who present initially with autoimmunity, especially autoimmune cytopenia. Such patients should be managed with extra care since they are at a higher risk of death.